Manufacturing method of rare earth-based sintered magnet

In the manufacturing process of R-T-B silicon shaping magnet, the second powder slurry is generated and the second pressing is performed under higher pressure in the manufacturing process of R-T-B silicon shaping magnets, and the problem of degradation of magnetic properties caused by long-term disassembly and reusing defective powders in the prior art is solved, and efficient magnetic properties are achieved.

JP2025055364APending Publication Date: 2025-04-08PROTERIAL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023164649
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is used to disassemble and reuse defective powder of R-T-B silicon shaping magnets, which leads to a long time, resulting in a degradation of magnetic properties.

Method used

Using a manufacturing method, it includes producing a first powder slurry, using the powder slurry to perform a first pressing in a magnetic field, creating and cutting a first powder shaping body, and then pulverizing and separating the cut residue to produce a second powder slurry and performing a second pressing at a higher pressure.

Benefits of technology

Even if the separation time of the powder is shortened, the magnetic properties are not damaged, and higher magnetic properties can be obtained by increasing the pressure of the second pressing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025055364000001_ABST
    Figure 2025055364000001_ABST
Patent Text Reader

Abstract

To provide a manufacturing method of a rare earth-based sintered magnet of which the magnetic characteristics are not deteriorated even if a cracking time is short when cracking and recycling a defective article of a powder compact, etc.SOLUTION: A manufacturing method of a rare earth-based sintered magnet includes: the step of preparing first powder slurry containing powder of a rare earth-based alloy; a first press step of using the first powder slurry to prepare a first powder compact in a magnetic field; the step of obtaining a cracking target including at least one of a defective article of the first powder compact, a defective article of the first powder compact piece obtained by cutting the first powder compact and the remainder obtained by cutting the first powder compact; the step of preparing second powder slurry of a rare earth-based alloy by cracking the cracking target in an oil solution; and a second press step of using the second powder slurry to prepare a second powder compact in the magnetic field. The press pressure in the second press step is higher than the press pressure in the first press step by 0.1 ton / cm2 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a rare earth sintered magnet. [Background technology]

[0002] RTB sintered magnets (R is at least one rare earth element, T is at least one transition metal element and always includes Fe, and B is boron), a representative example of rare earth sintered magnets, are known as the most high-performance magnets among permanent magnets, and are used in a variety of motors, including electric vehicle motors (EV, HV, PHV, etc.), industrial equipment motors, and home appliances. RTB sintered magnets are mainly R2T 14 It is composed of a main phase made of B compounds and a grain boundary phase (hereinafter sometimes simply referred to as "grain boundary") located at the grain boundary portion of this main phase. 14 The B compound is a ferromagnetic phase with high magnetization.

[0003] RTB sintered magnets can be manufactured through the following steps: (1) Melting (melting) raw materials such as metals to produce a molten alloy, which is then cooled and solidified by strip casting or another method to produce a raw alloy cast material with the desired composition; (2) Crushing the raw alloy cast material to produce alloy powder with a specified particle size (particle size distribution); (3) Pressing the alloy powder by a wet compacting method or another method to produce a powder compact; and (4) Sintering the powder compact to produce a sintered body.

[0004] In the stage of the powder compact, for example, when the powder compact comes into contact with something during handling such as transportation, a part of the powder compact may be chipped, resulting in a defective product. Also, a defective product may be caused by a crack occurring in the powder compact due to a problem during press molding. In addition, in order to avoid increasing the number of types of dies used in press molding, a relatively large block-shaped powder compact may be produced by press molding, and then the powder compact may be cut to produce compact pieces having the desired shape and size. In such cases, a part of the block-shaped powder compact remains as a "compact scrap" that is not sintered.

[0005] Since the rare earth elements used in RTB sintered magnets are scarce, it is preferable to effectively reuse defective moldings and molding scraps.

[0006] Patent Document 1 discloses a technique for crushing a powder compact for a rare earth sintered magnet formed from a rare earth element-containing powder over a period of time in oil so that the particle size of the powder particles does not change. In general, "crushing" means applying an external force to secondary particles formed by agglomeration of a large number of finely pulverized powder particles (primary particles) that constitute the rare earth element-containing powder to break the agglomeration and return them to a state of separated primary particles. Unlike grinding, crushing does not change the particle size of the primary particles. This technique makes it possible to regenerate a slurry of a rare earth element-containing powder from defective moldings, etc. Patent Document 1 also describes that the magnetic properties of a rare earth sintered magnet produced using the recycled slurry are at the same level as the magnetic property changes of a rare earth sintered magnet produced by a normal method. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2011 / 125578 Summary of the Invention [Problem to be solved by the invention]

[0008] The conventional technology disclosed in Patent Document 1 has a problem in that it takes a long time for disintegration.

[0009] An embodiment of the present disclosure provides a method for producing a rare earth sintered magnet in which, when defective powder compacts are crushed and reused, the magnetic properties do not deteriorate even if the crushing time is shortened. [Means for solving the problem]

[0010] In one embodiment, a method for producing a rare earth sintered magnet according to the present disclosure includes the steps of: preparing a first powder slurry containing a rare earth alloy powder; a first pressing step of producing a first powder compact in a magnetic field using the first powder slurry; obtaining a crushed object including at least one of a defective first powder compact, a defective first powder compact piece obtained by cutting the first powder compact, and a remainder obtained by cutting the first powder compact; crushing the crushed object in an oil agent to prepare a second powder slurry of the rare earth alloy; and a second pressing step of producing a second powder compact in a magnetic field using the second powder slurry, wherein the pressing pressure in the second pressing step is 0.1 ton / cm higher than the pressing pressure in the first pressing step. 2 More expensive than that. Effect of the Invention

[0011] According to the embodiments of the present disclosure, when defective powder compacts are crushed and reused, the magnetic properties are not deteriorated even if the crushing time is shortened. [Brief description of the drawings]

[0012] [Figure 1] 1 is a flowchart outlining a method for producing a rare earth sintered magnet according to an embodiment of the present disclosure. [Figure 2A] FIG. 11 is a front view for explaining a step of cutting the powder compact with a wire. [Figure 2B] FIG. 11 is another front view illustrating the step of cutting the powder compact with a wire. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] An outline of the manufacturing method of the rare earth sintered magnet of this embodiment will be described with reference to Fig. 1. As shown in Fig. 1, the manufacturing method of the rare earth sintered magnet of this embodiment includes a step (S10) of preparing a first powder slurry containing a rare earth alloy powder, a first pressing step (S12) of preparing a first powder compact in a magnetic field using the first powder slurry, a step (S14) of obtaining a crushed object including at least one of a defective first powder compact, a defective first powder compact piece obtained by cutting the first powder compact, and a remaining part obtained by cutting the first powder compact, a step (S16) of crushing the crushed object in an oil agent to prepare a second powder slurry of the rare earth alloy, and a second pressing step (S18) of preparing a second powder compact in a magnetic field using the second powder slurry. The pressing pressure in the second pressing step is 0.1 ton / cm higher than the pressing pressure in the first pressing step. 2 More expensive than that.

[0014] In the present disclosure, "disintegration" broadly includes applying an external force to secondary particles formed by agglomeration of many primary particles to disintegrate part of the agglomeration, thereby forming secondary particles smaller than the original secondary particles. In other words, "disintegration" in the present disclosure is not limited to returning to a state of primary particles separated from each other. Therefore, in the disintegration process in the embodiment of the present disclosure, smaller secondary particles are obtained from the secondary particles before disintegration. The higher the degree of disintegration, the smaller the secondary particles obtained, and in the case of the highest degree of disintegration, the particles are returned to the state of primary particles (finely pulverized powder particles before being pressed). The size of the secondary particles is evaluated by the size of the sieve openings.

[0015] Hereinafter, each step in the manufacturing method of this embodiment, including the above steps, will be described.

[0016] <Step of forming rare earth alloy powder> In this embodiment, a step of forming rare earth alloy powder by a jet mill pulverizing device is performed as a step of pulverizing the raw alloy to obtain rare earth alloy powder (fine pulverizing step). Prior to the fine pulverizing step, a hydrogen pulverizing step is preferably performed to prepare coarsely pulverized rare earth alloy powder. Here, the composition of the rare earth alloy raw material is, for example, as follows: R: 26.5 to 35 mass% (R is a rare earth element and necessarily contains at least one of Nd and Pr), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85~1.10% by mass, T: 61.5 mass % or more (T is Fe and Co, and 90% or more of T is Fe in terms of mass ratio).

[0017] The rare earth-based raw alloy having the above composition can be produced, for example, by a strip casting method, etc. The rare earth-based alloy may contain a plurality of types of alloy components having different compositions.

[0018] The hydrogen pulverization process may include a hydrogen absorption process in which hydrogen is absorbed into the rare earth alloy at a temperature of 200°C or less in a treatment chamber, and a dehydrogenation process in which hydrogen is exhausted from inside the treatment chamber and the rare earth alloy is heated to a temperature in the range of, for example, 80°C or more and 650°C or less to perform a dehydrogenation process and produce a coarsely pulverized powder.

[0019] The average particle size of the coarsely pulverized powder is, for example, 10 μm or more and 500 μm or less. The average particle size (d50) in this disclosure can be measured by an airflow dispersion type laser diffraction method (based on JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size means the particle size (median diameter: d50) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.

[0020] In the fine pulverization step, the coarsely pulverized powder is pulverized to obtain a fine powder having a median diameter d50 of, for example, 6.0 μm or less. The fine pulverization step may include a step of mixing an organic grinding aid with the coarsely pulverized powder. An example of the organic grinding aid is paraffin wax. The average particle size d50 of the finely pulverized powder is preferably 2.0 μm or more and 3.5 μm or less.

[0021] <Step of preparing first powder slurry (S10)> A slurry (first powder slurry) is prepared by mixing the finely pulverized powder with an oil agent. The oil agent is a liquid that can obtain a slurry by dispersing the alloy powder therein. A preferred oil agent used in the present disclosure can be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increase in viscosity strengthens the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet molding in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. Furthermore, if the fractional point of the mineral oil or synthetic oil exceeds 400°C, it becomes difficult to remove the oil after obtaining a compact, and the amount of residual carbon in the sintered body increases, which may result in a deterioration of the magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. Vegetable oil may also be used as the oil agent. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.

[0022] The mixing ratio of the alloy powder and the oil is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. 3 This is because at a flow rate of 1 / sec, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less in terms of mass ratio.

[0023] The method of mixing the alloy powder and the oil is not particularly limited. The alloy powder and the oil may be prepared separately, and then the alloy powder and the oil may be weighed and mixed together in a predetermined amount. When the coarsely pulverized powder is dry-pulverized with a jet mill or the like to obtain the alloy powder, a recovery container containing the oil may be placed at the alloy powder outlet of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization may be directly recovered in the oil in the recovery container to obtain a slurry. In this case, it is preferable that the atmosphere inside the recovery container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly recovered in the oil without being exposed to the air to obtain a slurry. Furthermore, it is also possible to wet-pulverize the coarsely pulverized powder in the oil using a vibration mill, ball mill, attritor, or the like to obtain a first powder slurry consisting of the alloy powder and the oil.

[0024] <First pressing step (S12) of producing a first powder compact> The slurry (first powder slurry) thus obtained is molded in a known wet press apparatus to obtain a powder compact (first powder compact) having a predetermined size and shape (first press step). Specifically, the first powder slurry is supplied to a cavity in a die of the wet press molding apparatus and press molded by applying a predetermined pressure in a magnetic field to produce the first powder compact. The pressing pressure in the first press step is 0.2 to 2.0 ton / cm. 2 The powder compact obtained in the first pressing step has a density of, for example, 4 g / cm 3 More than 5g / cm 3 It may have the following densities:

[0025] In this embodiment, the powder compact is formed in a magnetic field by wet pressing. In wet pressing, the surface of the particles constituting the powder compact is covered with an oil agent, and contact with oxygen and water vapor in the air is suppressed. Therefore, it is possible to prevent or suppress the particles from being oxidized by the air before, during, or after the pressing process. The production of the first powder compact may result in a defective first powder compact. The defective first powder compact refers to cracks, breaks, chips, and the like of the first powder compact that occur due to the density of the first powder compact becoming non-uniform during molding, or strong stress acting when the first powder compact is removed from the die.

[0026] <Step of cutting the powder compact> In this embodiment, the first powder compact obtained by the above process is cut by, for example, a wire saw device (cutting device) to produce one or more first powder compact pieces having dimensions smaller than the first powder compact. More specifically, the first powder compact of the rare earth-based raw alloy is placed in the oil of the wire saw device storing the oil, and the first powder compact is cut in the oil. By cutting the first powder compact, defective first powder compact pieces obtained by cutting the first powder compact and remnants obtained by cutting the first powder compact may be generated. The defective first powder compact pieces obtained by cutting the first powder compact refer to dimensional defects that occur when the first powder compact cannot be processed to the target dimensions due to a trouble with the device when cutting the first powder compact, or cracks, cracks, and chips in the first powder compact pieces that occur due to contact with the device or the first powder compact pieces when removing the first powder compact after cutting. The remainder obtained by cutting the first powder compact refers to excess material (such as stems) remaining after cutting the first powder compact to obtain first powder compact pieces.

[0027] In the following description, the cutting of the first powder compact 10 may be performed, for example, by a wire saw device 100 shown in FIG. 2A and FIG. 2B. FIG. 2A and FIG. 2B are front views for explaining the process of cutting the first powder compact 10 submerged in the oil agent 60 with a wire 40. FIG. 2A shows a state before the cutting process starts, and FIG. 2B shows a state during the cutting process. The dashed line in the first powder compact 10 shown in FIG. 2B shows a schematic representation of the position of the wire 40 while cutting the first powder compact 10. For reference, the figure shows an X-axis, a Y-axis, and an X-axis that are perpendicular to each other. In this example, the XY plane is horizontal, and the Z-axis is oriented vertically.

[0028] In this embodiment, the wire saw device 100 has rollers 30a, 30b, and 30c arranged so that the central axes of rotation are parallel to each other, and a single continuous wire 40. Each of the rollers 30a to 30c is rotatably supported by a support device (not shown). The rotation axes of the rollers 30a to 30c are parallel to the Y-axis. The wire 40 runs under tension due to the rotation of the rollers 30a to 30c. The wire 40 is wound up on a bobbin (not shown) or the like. The wire saw device 100 may further include other rollers for adjusting the tension, etc.

[0029] The first powder compact 10 is fixed to a fixing base 20 and placed inside a tank 62 that stores an oil agent 60. The entire first powder compact 10 is immersed in the oil agent 60. A portion of the traveling wire 40 that is located between rollers 30a and 30b contacts the first powder compact 10. A supporting device (not shown) has a shape that allows it to move in the Y-axis direction without interfering with the first powder compact 10 when the first powder compact 10 is being cut by the wire 40 traveling between rollers 30a and 30b.

[0030] In the illustrated example, the wire 40 travels in the X-axis direction at a predetermined speed, while moving in a direction perpendicular to the traveling direction of the wire 40 (any direction in the YZ plane). The direction perpendicular to the traveling direction of the wire 40 is the cutting direction, and the speed in this direction (cutting speed) is set to, for example, 100 mm / min or more. The example shown in FIG. 2B shows a state in which the traveling wire 40 moves, for example, in the negative direction of the Z-axis relative to the first powder compact 10 in a stationary state, but as described above, the first powder compact 10 may be lifted together with the fixing base 20 in the positive direction of the Z-axis, or may have a movement component in the Y-axis direction.

[0031] According to the wire saw device 100, one or more pieces of compacts having various shapes, possibly including curved surfaces, can be produced from a block-like first powder compact 10 having, for example, a rectangular parallelepiped shape. At this time, unsintered waste material is also produced from each of the first powder compacts 10.

[0032] <Step of obtaining crushed object (S14)> In this embodiment, the waste material formed from such a first powder compact is crushed in oil by a crushing device and reused to produce a new powder compact (second powder compact). Note that the reusable powder is not limited to a part of the first powder compact after cutting. Defective first powder compacts, defective first powder compact pieces obtained by cutting the first powder compact, and the remaining part obtained by cutting the first powder compact can all be reused as "materials to be crushed."

[0033] <Step of preparing second powder slurry (S16)> The object to be crushed is crushed in an oil to prepare a second powder slurry. Crushing in an oil is not limited to a state in which the compact is completely immersed in the oil, but includes a state in which the surface of the powder particles is covered with a film of oil sufficient to prevent contact with oxygen in the air. The oil is a mineral oil or a synthetic oil. The oil may be exactly the same as the oil used as the dispersion medium of the slurry described above, or may be different. The crushing can be performed using an apparatus such as that described in WO 2011 / 125578 or WO 2013 / 047429.

[0034] The longer the time of the crushing process, the more the crushing in the second powder slurry progresses, so that the powder particles in the second powder slurry can pass through a sieve with a small mesh size. As described above, it was previously believed that crushing should be performed until the powder particles in the second powder slurry pass through a sieve with a mesh size of 25 μm. In this embodiment, the powder particles in the second powder slurry after crushing are crushed to a state where they do not pass through a sieve with a mesh size of 25 μm, but pass through a sieve with a mesh size of 500 μm. The inventor's study has revealed that even in such an insufficiently crushed state, the magnet characteristics can be maintained at a high level by appropriately controlling the relationship between the pressing pressure in the first pressing process for producing the first powder compact and the pressing pressure in the second pressing process for producing the second powder compact. The following examples will be described in detail.

[0035] In the second powder slurry after crushing, the powder particles may be crushed to a state in which they do not pass through a sieve with 32 μm openings. This allows the crushing step to be completed in a shorter time, while still maintaining the properties of the final rare earth sintered magnet at a high level.

[0036] In the second powder slurry after crushing, the powder particles are preferably crushed to a state where they can pass through a sieve with an opening of 300 μm, and more preferably to a state where they can pass through a sieve with an opening of 100 μm.

[0037] <Second pressing step (S18) of producing a second powder compact> A second pressing step is carried out to produce a second powder compact in a magnetic field using the second powder slurry obtained by the above-mentioned crushing step. At this time, the pressing pressure in the second pressing step is 0.1 ton / cm higher than the pressing pressure in the first pressing step. 2 Set it to above.

[0038] The pressure in the first press process is 0.2 to 1.5 ton / cm 2 In this case, the pressing pressure in the second pressing step is 0.3 to 1.6 ton / cm 2 In addition, it is preferable that the pressing pressure in the second pressing step is 0.2 ton / cm higher than the pressing pressure in the first pressing step. 2 The pressure in the first press step is set to 0.2 to 0.4 ton / cm or more. This can suppress the decrease in Br. 2 In this case, the pressing pressure in the second pressing step is 0.4 to 0.6 ton / cm 2 It is preferable that:

[0039] In the second pressing step, a second powder compact may be produced from a mixed slurry of the first powder slurry and the second powder slurry. For example, the weight ratio of the second powder slurry in the mixed slurry is 30% or more. This weight ratio may be 80% or more.

[0040] The rare earth alloy powder particles contained in the first powder slurry are in a state capable of passing through a sieve with 25 μm openings.

[0041] <Process for producing rare earth sintered magnet material> Next, the second powder compact is sintered to obtain a rare earth sintered magnet body (sintered body).

[0042] The powder compact is preferably sintered at a pressure of 0.13 Pa (10 -3 Torr) or less, preferably 0.07 Pa (5.0 x 10 -4The sintering is carried out at a pressure of 1000 to 1150 Torr or less and at a temperature of 1000 to 1150°C. To prevent oxidation due to sintering, residual gas in the atmosphere may be replaced with an inert gas such as helium or argon. The obtained sintered body is preferably subjected to a heat treatment. The magnetic properties can be improved by the heat treatment. Known conditions for the heat treatment, such as the heat treatment temperature and heat treatment time, can be adopted. The rare earth sintered magnet body thus obtained is subjected to an element diffusion step in which various elements are diffused from the surface of the rare earth sintered magnet body to the inside, a heat treatment step, a grinding and polishing step, a surface treatment step, and a magnetization step, as necessary, to complete the final rare earth sintered magnet.

[0043] According to the embodiment of the present disclosure, the time required for the crushing step is shortened to reduce the degree of crushing, but the pressing pressure in the second pressing step is made higher than the pressing pressure in the first pressing step, thereby making it possible to use a relatively high pressing pressure (for example, 0.5 ton / cm 2 This makes it possible to obtain superior magnetic properties compared to when a single pressing process is performed. EXAMPLES

[0044] The present disclosure will be described in further detail below with reference to experimental examples (including examples and comparative examples); however, the present disclosure is not limited thereto.

[0045] First, the raw materials of each element were weighed so that the rare earth sintered magnet (RTB sintered magnet) would have the composition shown in Table 1, and an alloy was produced by strip casting. The obtained alloys were coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powder. Next, 0.04 mass% of paraffin wax was added as a lubricant to the obtained coarsely pulverized powder relative to 100 mass% of the coarsely pulverized powder, and after mixing, the mixture was dry-pulverized in a nitrogen stream using an airflow pulverizer (jet mill device). The average particle size d50 of the finely pulverized powder was 2.7 μm.

[0046] [Table 1]

[0047] The first powder slurry was obtained by adding and mixing the finely pulverized powder and mineral oil having a kinetic viscosity of 2 cSt at room temperature as an oil agent and 1.6% by mass of liquid lubricant to 100% by mass of the finely pulverized powder. The concentration of the finely pulverized powder in the slurry in this embodiment was 75% by mass.

[0048] Next, the first powder slurry was pressed in a magnetic field using a press molding device to produce a first powder compact (first press step). As the press molding device, a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure application direction are perpendicular to each other was used. The applied pressure (first press pressure) was 0.3 ton / cm. 2 , or 0.5 ton / cm 2 The strength of the applied magnetic field was 1.6 T (tesla).

[0049] After that, a stainless steel container containing oil was prepared in a box under a nitrogen atmosphere, and the above-mentioned green compact was immersed in the oil while being crushed from above with another stainless steel container to crush the first powder green compact, thereby producing a second powder slurry. The second powder slurry is divided into the following four sample groups based on the degree of crushing. Slurry A: Does not pass through a 100 μm sieve, but passes through a 300 μm sieve Slurry B: Does not pass through a sieve with 300 μm openings, but passes through a sieve with 500 μm openings Slurry R: First powder slurry (standard example)

[0050] The slurry R is the first powder slurry, and has not been subjected to compaction in a magnetic field or crushing. According to the inventors, the pressing pressure in the first pressing step is 0.3 ton / cm 2 In the case where the pressing pressure in the first pressing process is 0.5 ton / cm 2In both cases, it has been confirmed that the same amount of slurry A can be obtained in about one-fourth or less of the time required for crushing to about slurry R, ​​that is, until the powder particles in the second powder slurry pass through a sieve with 25 μm openings, and the same amount of slurry B can be obtained in about one-fifth or less of the time required for crushing. Therefore, the time required for crushing slurry A and slurry B is significantly shorter than when crushing to about slurry R.

[0051] Next, the above slurries A, B, and R were each supplied as a second powder slurry to the press molding apparatus, and the second powder slurry was pressed in a magnetic field to produce a second powder compact (second pressing step).

[0052] The obtained compact was sintered in a vacuum at 1040°C for 4 hours to obtain a rare earth sintered magnet. The rare earth sintered compact was then heat treated at 800°C for 2 hours. The density of the obtained rare earth sintered magnet was 7.5 Mg / m 3 That was all.

[0053] The obtained rare earth sintered magnet was machined to a sample of 7.0 mm × 7.0 mm × 7.0 mm, and the residual magnetic flux density B r (Unit: Tesla (T)) was measured.

[0054] Table 2 shows the press pressure in the second press process at 0.3 ton / cm 2 B of samples 1 to 5 r and B of sample 1, which is the standard r The results are based on a judgment that those that are equivalent (even if they have decreased, they are less than 0.15T) are sufficient (○), and those that have decreased by 0.015T or more are insufficient (×).

[0055] [Table 2]

[0056] As can be seen from Table 2, the press pressure in the first press process (0.5 ton / cm 2The press pressure in the second press process is lower than that in the first press (0.3 ton / cm 2 ), the press pressure in the first press process (0.3 ton / cm 2 ) and the press pressure in the second press process (0.3 ton / cm 2 ) is equal, slurry B and slurry C that have been passed through a coarse sieve have a smaller B than the standard. r is declining.

[0057] However, as a result of further investigation by the present inventors, it was found that results different from the above results could be obtained by changing the pressing pressure.

[0058] Table 3 shows the results when the pressing pressure in the second pressing process was 0.5 ton / cm 2 B of samples 11 to 15 r and the standard sample 11, B r The results are based on a judgment that those that are equivalent (even if they have decreased, they are less than 0.15T) are sufficient (○), and those that have decreased by 0.015T or more are insufficient (×).

[0059] [Table 3]

[0060] As can be seen from Table 3, the press pressure in the first press process (0.5 ton / cm 2 ) and the press pressure in the second press process (0.5 ton / cm 2 ) is equal to the standard, similar to samples 4 and 5 in Table 2. r On the other hand, the press pressure in the first press process (0.3 ton / cm 2 The press pressure in the second press process is higher than that in the first press process (0.5 ton / cm 2 ) If there is sufficient B for the reference sample 11, r was obtained.

[0061] The above results indicate that when the degree of crushing is low and the secondary particles are large, they come into contact with other secondary particles and are subject to frictional forces, making it difficult for the magnetization easy direction of the large secondary particles to be oriented in the direction of the applied magnetic field during molding, and therefore sufficient B r However, by setting the pressing pressure in the second pressing step higher than that in the first pressing step, the secondary particles were mechanically crushed during the second pressing step and became smaller in size, which made it easier for them to be oriented in the direction of the applied magnetic field, and therefore sufficient B r It is believed that the following was obtained.

[0062] As a result of further investigation by the inventors, it was found that the pressing pressure in the second pressing step was 0.1 ton / cm higher than the pressing pressure in the first pressing step. 2 It was found that similar effects could be obtained if the pressure in the first press step was set to 0.2 to 1.5 ton / cm. 2 In this case, the pressing pressure in the second pressing step is 0.3 to 1.6 ton / cm 2 It is preferable that the pressing pressure in the first pressing step is 0.2 to 0.4 ton / cm. 2 In this case, the pressing pressure in the second pressing step is 0.4 to 0.6 ton / cm 2 It is preferable that:

[0063] In the second pressing process, the second powder compact may be produced from a mixed slurry of the first powder slurry and the second powder slurry. In the case of mixing, the weight ratio of the second powder slurry in the mixed slurry must be 30% or more, and preferably 80% or more.

[0064] According to this embodiment, there is no need to crush the secondary particles in the second powder slurry to the same size as the secondary particles in the first powder slurry, and it is possible to shorten the crushing time to, for example, one-quarter or less without degrading the magnetic properties.

[0065] As described above, the present disclosure includes the methods for producing sintered rare earth magnets described in the following items. [Item 1] preparing a first powder slurry containing a rare earth alloy powder; a first pressing step of producing a first powder compact in a magnetic field using the first powder slurry; obtaining a crushing target including at least one of a defective first powder compact, a defective first powder compact piece obtained by cutting the first powder compact, and a remainder obtained by cutting the first powder compact; disintegrating the object to be disintegrated in an oil agent to prepare a second powder slurry of the rare earth alloy; a second pressing step of producing a second powder compact in a magnetic field using the second powder slurry; Including, The pressing pressure in the second pressing step is 0.1 ton / cm higher than the pressing pressure in the first pressing step. 2 A method for producing rare earth sintered magnets having a high production efficiency. [Item 2] 2. The method for producing a rare earth sintered magnet according to item 1, wherein the second powder slurry is pulverized so that the powder particles do not pass through a sieve with openings of 25 μm but pass through a sieve with openings of 500 μm. [Item 3] 3. The method for producing a rare earth sintered magnet according to any one of items 1 to 2, wherein in the second powder slurry, the powder particles are pulverized to a state capable of passing through a sieve having an opening of 300 μm. [Item 4] 4. The method for producing a rare earth sintered magnet according to any one of items 1 to 3, wherein in the second powder slurry, the powder particles are pulverized to a state capable of passing through a sieve having an opening of 100 μm. [Item 5] The pressing pressure in the first pressing step is 0.2 to 1.5 ton / cm 2 and The pressing pressure in the second pressing step is 0.3 to 1.6 ton / cm 2 5. The method for producing a rare earth sintered magnet according to any one of items 1 to 4, [Item 6] The pressing pressure in the first pressing step is 0.2 to 0.4 ton / cm 2 and The pressing pressure in the second pressing step is 0.4 to 0.6 ton / cm 2 6. The method for producing a rare earth sintered magnet according to any one of items 1 to 5, [Item 7] In the second pressing step, the second powder compact is produced from a mixed slurry of the first powder slurry and the second powder slurry; 7. The method for producing a rare earth sintered magnet according to any one of items 1 to 6, wherein a weight ratio of the second powder slurry in the mixed slurry is 30% or more. [Item 8] 8. The method for producing a rare earth sintered magnet according to any one of items 1 to 7, wherein a weight ratio of the second powder slurry in the mixed slurry is 80% or more. [Item 9] 9. The method for producing a rare earth sintered magnet according to any one of items 1 to 8, wherein the rare earth alloy powder particles contained in the first powder slurry are in a state that allows them to pass through a sieve with 25 μm openings.

Claims

1. preparing a first powder slurry containing a rare earth alloy powder; a first pressing step of producing a first powder compact in a magnetic field using the first powder slurry; obtaining a crushing target including at least one of a defective first powder compact, a defective first powder compact piece obtained by cutting the first powder compact, and a remainder obtained by cutting the first powder compact; disintegrating the object to be disintegrated in an oil to prepare a second powder slurry of the rare earth alloy; a second pressing step of producing a second powder compact in a magnetic field using the second powder slurry; Including, The pressing pressure in the second pressing step is 0.1 ton / cm higher than the pressing pressure in the first pressing step. 2 A method for producing rare earth sintered magnets having a high production efficiency.

2. 2. The method for producing a rare earth sintered magnet according to claim 1, wherein the second powder slurry is pulverized so that the powder particles do not pass through a sieve with an opening of 25 μm but pass through a sieve with an opening of 500 μm.

3. 3. The method for producing a rare earth sintered magnet according to claim 2, wherein the powder particles in the second powder slurry are pulverized to a state capable of passing through a sieve having an opening of 300 μm.

4. 4. The method for producing a rare earth sintered magnet according to claim 3, wherein the powder particles in the second powder slurry are pulverized to a state capable of passing through a sieve having an opening of 100 μm.

5. The pressing pressure in the first pressing step is 0.2 to 1.5 ton / cm 2 and The pressing pressure in the second pressing step is 0.3 to 1.6 ton / cm 2 The method for producing a rare earth sintered magnet according to claim 1,

6. The pressing pressure in the first pressing step is 0.2 to 0.4 ton / cm 2 and The pressing pressure in the second pressing step is 0.4 to 0.6 ton / cm 2 The method for producing a rare earth sintered magnet according to claim 5 ,

7. In the second pressing step, the second powder compact is produced from a mixed slurry of the first powder slurry and the second powder slurry; 2. The method for producing a rare earth sintered magnet according to claim 1, wherein a weight ratio of said second powder slurry in said mixed slurry is 30% or more.

8. 8. The method for producing a rare earth sintered magnet according to claim 7, wherein a weight ratio of said second powder slurry in said mixed slurry is 80% or more.

9. 9. The method for producing a rare earth sintered magnet according to claim 1, wherein the rare earth alloy powder particles contained in the first powder slurry are capable of passing through a sieve having an opening size of 25 μm.

Citation Information

Patent Citations

  • Method for recycling slurry, method for manufacturing rare-earth based sintered magnet, and apparatus for recycling slurry

    WO2011125578A1